Subjects and Narratives in Archaeology - Van Dyke, Ruth M.; Bernbeck, Reinhard, 1958- (Book collections on Project MUSE., 2015)
"Seeking to move beyond the customary limits of archaeological prose and representation, Subjects and Narratives in Archaeology presents archaeology in a variety of nontraditional formats. The volume demonstrates that visual art, creative nonfiction, archaeological fiction, video, drama, and other artistic pursuits have much to offer archaeological interpretation and analysis. Chapters in the volume are augmented by narrative, poetry, paintings, dialogues, online databases, videos, audio files, and slideshows. The work will be available in print and as an enhanced ebook that incorporates and showcases the multimedia elements in archaeological narrative. While exploring these new and not-so-new forms, the contributors discuss the boundaries and connections between empirical data and archaeological imagination. Both a critique and an experiment, Subjects and Narratives in Archaeology addresses the goals, advantages, and difficulties of alternative forms of archaeological representation. Exploring the idea that academically sound archaeology can be fun to create and read, the book takes a step beyond the boundaries of both traditional archaeology and traditional publishing"--